Peer sociocognitive interaction according to symmetry and asymmetry of epistemic competence - Castellaro, Mariano (2018)
The study aimed to analyze the peer sociocognitive interaction and its relationship with individual cognitive progress, in both symmetrical and asymmetrical situations of epistemic competence. Participants were 72 students of fifth and sixth grade (age, M = 11 years, 3 months, SD = 7 months), who solved logical items (pre / post test individual, intermediate dyadic condition). The results indicated: a) the distribution of arguments in the dyad is the main variable of the interactive process related to differences between symmetrical conditions and b) the volume and distribution of the arguments in dyads are significantly associated with individual cognitive advancement, independently of symmetrical/asymmetrical condition. The results are discussed from a socioconstructivist perspective.